Seed Morphometry of Native Indonesian Orchids in the Genus Dendrobium - Sucipto Hariyanto; Intan Ayu Pratiwi; Edy Setiti Wida Utami (Scientifica)
In this study, seeds of 10 species of epiphytic orchids were examined using light and scanning electron microscope. Quantitative and qualitative characters were analyzed. All the presently investigated seeds showed are transparent with visible embryo and remarkable embryo color variations (such as pale yellow, light yellow, shiny yellow to yellow, orange, and white). The species showed two groups in seed shape (fusiform and filiform), prolate and oval-shaped embryo, positioned at the center of the long axis and near apical pole. Embryo in prolate shaped and near apical pole position was only in D. antennatum. Based on our investigation, there are variations in seed and embryo volume as well as percentage air space in different taxa of orchids. The highest air space percentages were found in D. leporinum. According to the ornamentation of testa cells, 3 types of seeds were discovered in this genus. Additionally, the clear variation in the testa ornamentation pattern includes the species of D. leporinum, where the testa cells were in the medial regular rectangles, but in the apical and basal pole they are polygonal and irregularly oriented; the testa cells of D. antennatum are polygonal and irregularly oriented and those of D. purpureum are longitudinally oriented with regular rectangles.